2010
DOI: 10.5172/conu.2009.34.1.085
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a home-based pulmonary maintenance program for individuals with COPD: A pilot study

Abstract: This preliminary pilot study explores sustained benefits of pulmonary rehabilitation (PR) in people with chronic obstructive pulmonary disease (COPD) attending a 12 month home-based pulmonary maintenance program. The incidence of COPD is high and ageing populations will see this continue and possibly increase. PR programs are effective, however, benefits may dissipate if the program is not continued. The maintenance program involved: strength retraining exercises; collaborative goal setting; regular telephone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…One of the two‐one‐group pre–post studies evaluated partnership‐based nursing practice for people with COPD and found an improvement in SGRQ scores over time (MD = 3.9–20.2, p = 0.04 to <0.0001) for all the SGRQ subscores and total score (Ingadottir & Jonsdottir, ). The other one‐group pre–post study evaluated home‐based pulmonary rehabilitation and found no improvement over time in SGRQ scores (MD = −0.02 to −3.39, p = not reported) (Cooke et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the two‐one‐group pre–post studies evaluated partnership‐based nursing practice for people with COPD and found an improvement in SGRQ scores over time (MD = 3.9–20.2, p = 0.04 to <0.0001) for all the SGRQ subscores and total score (Ingadottir & Jonsdottir, ). The other one‐group pre–post study evaluated home‐based pulmonary rehabilitation and found no improvement over time in SGRQ scores (MD = −0.02 to −3.39, p = not reported) (Cooke et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in Turkey (Akinci & Olgun, 2011), Australia (Cooke, Moyle, Griffiths, & Shields, 2010;Wood-Baker, Reid, Robinson, & Walters, 2012), Iceland (Ingadottir & Jonsdottir, 2010), China (Liu et al, 2013), Japan (Moriyama, Takeshita, Haruta, Hattori, & Ezenwaka, 2015), Korea (Oh, 2003) In this category, one RCT was identified (Liu et al, 2013) and two studies with a two-group pre-post design (Akinci & Olgun, 2011;Moriyama et al, 2015). These three studies used the SGRQ and included an online video-based breathing programme (Liu et al, 2013), education about COPD and performance of breathing exercises and physical training (Akinci & Olgun, 2011), or a nurse-led self-management educational programme that included an interactive workbook, learning materials and journal for self-monitoring (Moriyama et al, 2015).…”
Section: Nursing Interventions Performed At Homementioning
confidence: 99%
“…The identification of such concepts facilitates placement of the chosen concept (QoL) within its context (COPD). Alexander and Wagner, 2012;Bentsen, Wentzel-Larsen, Henriksen, Rokne, and Wahl, 2010;Bentsen, Langeland, and Holm, 2012;Bentsen, Rokne, and Wahl, 2013;Bratås, Espnes, Rannestad, and Walstad, 2012;Cooke, Moyle, Griffiths, and Shields, 2009;Gellis et al, 2012;Hutchinson et al, 2010;Ingadottir and Jonsdottir, 2010;Kil, Oh, Koo, and Suk, 2010;Janssen, Spruit, Wouters, and Schols, 2012;Jeppesen et al, 2012;Lin et al, 2012;Nguyen, Donesky-Cuenco, and Carrieri-Kohlman, 2008;Wakabayashi et al, 2011;Warwick, Gallagher, Chenoweth, and Stein-Parbury, 2010;Wong, Carson, and Smith, 2012;Wood-Baker, Reid, Robinson, and Walters, 2012;…”
Section: Surrogate and Related Termsmentioning
confidence: 99%
“…Coping strategies Barnett, 2008;Blumenthal et al, 2009 Self-management Bentsen et al, 2012;Bischoff et al, 2012;Ingadottir and Jonsdottir, 2010;Warwick et al, 2010;Wood-Baker et al, 2012 Maintaining of physical and emotional aspects Chen, Chen, Lee, Cho, and Weng, 2008;Efraimsson et al, 2008 Exercise capacity Chan et al, 2010;Cooke et al, 2009 Positive mental attitude Cooke et al, 2009 Self-efficacy Cooke et al, 2009;Efraimsson et al, 2008;Wood-Baker et al, 2012 Disease characteristics Disease severity Ade-Oshifogun, 2012; Hrisanfow and Hägglund, 2013;van Dam van Isselt et al, 2013;Wilson et al, 2008 Symptomatology dyspnea Akinci et al, 2013;Alexander and Wagner, 2012;Bailey, 2008;Ek and Terneste...…”
Section: Surrogate and Related Termsmentioning
confidence: 99%
“…Although positive effects of PR on HRQoL as well as functional capacity are widely recognized (Cooke, Moyle, Griffiths & Shields, ; Wagg, ), maintaining all these benefits from PR in patients with COPD has been challenging in the face of the incurable and progressive nature of the disease (Jenkins, Hill & Cecins, ; Wagg, ).…”
Section: Introductionmentioning
confidence: 99%